Isolation and characterization of motile aeromonads from aquatic environment - Rathore, Gaurav; Swaminathan, T Raja; Abidi, Rehana; Mahanta, P C; Kapoor, D (Indian Journal of Fisheries, 2011)
Isolation and characterization of motile aeromonads from aquatic environment